Beta-mangostin demonstrates apoptogenesis in murine leukaemia (WEHI-3) cells in vitro and in vivo - Omer, FAA; Hashim, NM; Ibrahim, MY; Aldoubi, AF; Hassandarvish, P; Dehghan, F; Nordin, N; Karimian, H; Salim, LZA; Abdulla, MA; Al-Jashamy, K; Mohan, S (Biomed Central Ltd, 2024)
Background: Beta-mangostin (BM) is a xanthone-type of natural compound isolated from Cratoxylum arborescens. This study aimed to examine the apoptosis mechanisms induced by BM in a murine monomyelocytic cell line (WEHI-3) in vitro and in vivo. Methods: A WEHI-3 cell line was used to evaluate the cytotoxicity of BM by MTT. AO/PI and Hoechst 33342 dyes, Annexin V, multiparametric cytotoxicity 3 by high content screening (HCS); cell cycle tests were used to estimate the features of apoptosis and BM effects. Caspase 3 and 9 activities, ROS, western blot for Bcl2, and Bax were detected to study the mechanism of apoptosis. BALB/c mice injected with WEHI-3 cells were used to assess the apoptotic effect of BM in vivo. Results: BM suppressed the growth of WEHI-3 cells at an IC50 value of 14 +/- 3 mu g/mL in 24 h. The ROS production was increased inside the cells in the treated doses. Both caspases (9 and 3) were activated in treating WEHI-3 cells at 24, 48 and 72 h. Different signs of apoptosis were detected, such as cell membrane blebbing, DNA segmentation and changes in the asymmetry of the cell membrane. Another action by which BM could inhibit WEHI-3 cells is to restrain the cell cycle at the G(1)/G(0) phase. In the in vivo study, BM reduced the destructive effects of leukaemia on the spleen and liver by inducing apoptosis in leukaemic cells. Conclusion: BM exerts anti-leukaemic properties in vitro and in vivo.